ECONOMETRIC ANALYSIS OF THE ACTIVITIES OF MULTI-SECTORAL FARMS - Bustonov, Mansurjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Studies show that the demand for food products is expected to increase by 60 percent by 2050. This poses a serious challenge to agriculture and food systems around the world in the face of climate change, limited natural resources and the emergence of new types of demand. In developing countries, it is observed that small producers play a leading role as producers of most of the food to meet the needs. Results. Indeed, in Asian countries, small producers play a crucial role in meeting the demand for food. This is especially true during the Green Economy, when small farmers began to adopt new techniques, increase productivity, and produce enough food to lower and stabilize real consumer prices of staple foods. In rural areas, the demand for labor has increased, jobs have been created for the poor rural population, and their wages are increasing. A combination of these factors helped ensure food security for all.